Factors That Influence The Entrepreneurial Intention Of UMKM Fashion In The East Jakarta Small Industry Center - Rahayu, Puspita; Parashakti, Ryani Dhyan (Lentera Ilmu Nusantara, 2023)
The main objective of this study is to determine the factors that influence entrepreneurial intention. The research design uses a causal quantitative descriptive approach. The objects in this study were fashion traders as many as 100 respondents at the Small Industry Center. The data collection method uses questionnaires distributed to fashion traders. Data analysis in this study used multiple linear regression analysis, classical assumption test, r square test and hypothesis test, using the SPSS 26 data processing tool. The first stage in this research is to determine the indicators for each variable and compose statements that will be used as a questionnaire, then after the data is collected, it is tested for the validity of the questions for each variable along with its reliability. The second stage examines the relationship between entrepreneurial attitudes, entrepreneurship education, family factors, and entrepreneurial intentions. The next stage will measure the research results of each variable relationship.